Factors influencing the level of awareness towards motor Takaful amongst employees and customers of SOCSO / Norfateha Masri - Masri, Norfateha (Faculty of Business and Management, 2011)
This study focused on factors influencing the level of knowledge towards Motor Takaful amongst employees and customers of SOCSO. Since everyone familiar with Takaful but they do not know how Motor Takaful may operate. Actually, there have three types of Takaful certificates for motor vehicles available in market. They are Motor Takaful for Private Car, Motor Takaful for Private Motorcycle and Motor Takaful for Commercial Vehicles.